2020
DOI: 10.3389/fpsyg.2020.00061
|View full text |Cite
|
Sign up to set email alerts
|

The Transgenerational Consequences of the Interaction Between Humans and Molecules: Alcohol as a Cultural Artifact

Abstract: With drinking, I cancel all my troubles; What does it matter if I am poor? When I drink I am as rich as the rich Croesus. I really want to sing while I'm lying down, crowned with ivy. Here: I am the master of the world and if you want, o soldier, goes to war too. When you have fallen, pierced, I will be drunk, yes, but far more alive than you (Anacreon, 5th cent. B.C.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Notably, Hausknecht et al (2015) reported an enhanced excitatory synaptic strength in the ventral tegmental area dopamine neurons associated with drug addiction due to PAE that persists from infancy through to adulthood in rats (2–12 weeks). This implies that PAE modifies the reward system such that its plastic responses are persistently altered (Granato, 2020). Hence, the mu‐opioid receptor (MOR) may be involved in the programming effect of PAE as alcohol‐induced β‐endorphins stimulate the MOR believed to cause the release of dopamine in the brain reward system (Herz, 1997).…”
Section: Prenatal Alcohol Consumption: Mechanisms To Aldmentioning
confidence: 99%
“…Notably, Hausknecht et al (2015) reported an enhanced excitatory synaptic strength in the ventral tegmental area dopamine neurons associated with drug addiction due to PAE that persists from infancy through to adulthood in rats (2–12 weeks). This implies that PAE modifies the reward system such that its plastic responses are persistently altered (Granato, 2020). Hence, the mu‐opioid receptor (MOR) may be involved in the programming effect of PAE as alcohol‐induced β‐endorphins stimulate the MOR believed to cause the release of dopamine in the brain reward system (Herz, 1997).…”
Section: Prenatal Alcohol Consumption: Mechanisms To Aldmentioning
confidence: 99%
“…In support of this hypothesis, lacosamide, an antiepileptic drug, prohibits CRMP2-mediated microtubule assembly which underlies addiction-like behavior. 76 Given mounting evidence that FASD is associated with increased propensity for substance use disorders, 78 this could be a critical mechanism to investigate.…”
Section: Introductionmentioning
confidence: 99%